SITE OCCUPANCY OF TRANSITION ELEMENTS IN C15 NBCR2 LAVES PHASE: A FIRST-PRINCIPLES STUDY - Long, Qianxin; Wang, Jianchuan; Yong, Du; Nie, Xiaowu; Jin, Zhanpeng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Using first-principles calculations, site occupancy behaviors of transition elements in C15 NbCr2 Laves phase are systematically investigated. Elements Y, Sc, Zr, Hf, Cd, Ta, Ti and Ag prefer to occupy the Nb site, and elements Zn, Pt, Re, Tc, Ir, V, Os, Rh, Ru, Ni, Co, Mn, Fe and Cu favor to occupy the Cr site; whereas elements Mo, W, Pd and Au have weak site preference for Cr or Nb site. The present calculations agree well with the available experimental and previously calculated results. The relation between site occupancy behavior and radii of transition elements is established. The relation shows that the site occupancy behavior of transition elements in NbCr2 is mainly affected by the radii of transition elements. The present calculations also propose the correlation between the site preference energy ( ) and radii of transition elements.